Influence of age, body mass index and comorbidity on major outcomes in acute pancreatitis, a prospective nation‐wide multicentre study. Issue 10 (1st December 2018) - Moran, Robert A; García-Rayado, Guillermo; de la Iglesia-García, Daniel; Martínez-Moneo, Emma; Fort-Martorell, Esther; Lauret-Braña, Eugenia; Concepción-Martín, Mar; Ausania, Fabio; Prieto-Martínez, Carlos; González-de-Cabo, Miguel; Quesada-Vázquez, Noé; Marcaide-Ruiz-de-Apodaca, M Asunción; et al.
Abstract : Background: There are few large prospective cohort studies evaluating predictors of outcomes in acute pancreatitis. Objectives: The purpose of this study was to determine the role of age and co‐morbid disease in predicting major outcomes in acute pancreatitis. Methods: Data points were collected according to a predefined electronic data collection form. Acute pancreatitis and its complications were defined according to the revised Atlanta classification. Univariable and multivariable analyses were conducted using Cox proportional hazard regression and multiple logistic regression. Results: From June 2013–February 2015, 1655 adult patients were recruited from 23 centres across Spain. Co‐morbid disease, obesity, open surgical necrosectomy within 30 days, and pancreatic necrosis were independently associated with both 30‐day mortality and persistent organ failure ( p < 0.05 for all). Age was not associated with persistent organ failure, however the extreme of age (>85 years) was associated with mortality ( p < 0.05). Co‐morbid disease and obesity were not independently associated with a prolonged length of stay or other markers of morbidity on adjusted analysis ( p > 0.05). Conclusion: Comorbidity and obesity are important determinates of mortality and persistent organ failure in acute pancreatitis, but in the absence of organ failure they do not appear to independently contribute to morbidity. This has important implications for severity classification and predictive models of severity in acute pancreatitis.